Sistem Pengendalian Pemungutan Pajak Hotel dan Pajak Restoran Beberapa Kabupaten di Propinsi Kalimantan Barat - Yuana S (STIE 'INDONESIA' Pontianak, 2016)
The formation of autonomous regions is intended to enable the areas concerned to organize and manage his own household well as improve the performance of local government administration in the framework of public service and implementation. Efforts to facilitate the machinery of government is dependent upon the ability of the region to explore and utilize all potentials as existing financial resources effectively and efficiently its region. In particular the hotel and restaurant tax tax must get supervision. Both these taxes have contributed greatly to the acceptance of PAD in local government. Implementation of the control system of tax collection and the hotel restaurant is quite effective tax can be seen from the analysis of the flowchart and the functioning of the existing organizational structure in DPPKAD